The Relationship between Concept Mastery and Scientific Literacy of High School Students' on Plant Growth and Development Concept - Baiq Muli Harisanti; Any Fatmawati; Titi Laily Hajiriah (Jurnal Penelitian Pendidikan IPA, 2024)
Scientific literacy and mastery of concepts are needed to prepare a generation that is ready and adaptive to face developments in science and technology in the 21st century. Therefore, there is a need to change the learning process through the application of appropriate learning models. The Project Based Learning (PjBL) model can be a solution in increasing students' scientific literacy and mastery of concepts. This research was conducted at SMAN 7 Mataram, West Nusa Tenggara (NTB) with a quasi experimental pretest-posttest design. The research subjects were 132 of the 10th grade students. The research instrument for scientific literacy and concept mastery uses essay questions. Data were analyzed descriptively and with inferential statistics, i.e correlation tests at a significance level of 1%. The results of data analysis show that the significance value is 0.00, so it can be concluded that there is a positive correlation between concept mastery and student literacy. The implication of the results of this research is that the use of the PjBL model can be used as an alternative model that can empower students' mastery of science concepts and literacy